Análise de registros ortográficos de consoantes soantes no início da alfabetização - Souza, Suellen Vaz de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
OBJECTIVES: describe children's orthographic performance, referring to the record of contrasts between sonorant consonants of Brazilian Portuguese in context of non-controlled production; verify if the non-conventional record of these consonants is influenced by the lexical accent; categorize the kinds of orthographic substitutions; verify if the substitutions involve elements from the large class of sonorant consonants; and verify what are the traces inherent to the sonorant consonants (nasal and liquid) more, or less, problematic in the orthographic record of these segments. METHODS: in this research, 801 text productions coming from the development of 14 different thematic proposals were selected. They were made by 76 children from the First Grade of Primary School, in 2001, at two schools of a paulista city. From these productions, all the words with the occurrence of sonorant consonants in a syllabic position of simple attack were selected. These occurrences were, then, organized according to their appearance in pre-tonic, tonic and post-tonic syllables, unstressed monosyllables and tonic monosyllables. RESULTS: it was noted: (i) amount of hits higher than the amount of mistakes; (ii) higher occurrence of mistakes in non-accented syllables; (iii) higher occurrence of phonological ortographic substitutions followed by ortographic omissions and, finally, not phonological orthographic substitutions; (iv) a higher number of occurrence of substitutions that involved graphemes related to the sonorant class; and (v) major difficulty with the trace [labial] - in the nasal subclass -, and with the trace [dorsal] - in the subclass of the liquids. CONCLUSION: despite the orthographic acquisition be related to the general characteristics of the acquisition of the language phonology, this relation is not direct, what indicates that the children support aspects that are not only phonological during the acquisition of the orthography.

OBJETIVOS: descrever o desempenho ortográfico de crianças, no que se refere ao registro de contrastes entre consoantes soantes do PB em contexto de produção não controlada; verificar se o registro não convencional dessas consoantes sofre influência do acento lexical; categorizar os tipos de substituições ortográficas; verificar se as substituições envolvem elementos da grande classe das consoantes soantes; e verificar quais os traços inerentes às subclasses das consoantes soantes (nasais e líquidas) mais, ou menos, problemáticos no registro ortográfico desses segmentos. MÉTODOS: para a presente pesquisa, foram selecionadas 801 produções textuais resultantes do desenvolvimento de 14 diferentes propostas temáticas, realizadas por 76 crianças da 1ª série do Ensino Fundamental, no ano de 2001, de duas escolas de um município paulista. Dessas produções, foram selecionadas todas as palavras com ocorrência de consoantes soantes em posição silábica de ataque simples. Essas ocorrências foram, então, organizadas conforme aparecessem em sílabas pré-tônicas, tônicas, pós-tônicas, monossílabos átonos e monossílabos tônicos. RESULTADOS: observou-se: (i) quantidade de acertos maior do que quantidade de erros; (ii) maior ocorrência de erros em sílabas não acentuadas; (iii) maior ocorrência de substituições ortográficas fonológicas seguida de omissões ortográficas e, por fim, de substituições ortográficas não fonológicas; (iv) maior número de ocorrência de substituições que envolveram grafemas que remetiam à classe das soantes; e (v) maior dificuldade com o traço [labial] - na subclasse das nasais -, e com o traço [dorsal] - na subclasse das líquidas. CONCLUSÃO: apesar de a aquisição ortográfica ter relação com características gerais da aquisição da fonologia da língua, essa relação não é direta, o que indica que as crianças se apoiam em aspectos que não apenas os de natureza...
Keywords: Escrita; Lingua portuguesa - Ortografia e silabação; Ensino fundamental; Fonoaudiologia; Fonologia; Phonology